Buya and religious issues in the 2019 presidential election in West Sumatra - Adlin Adlin (Faculty of Social and Political Science, Universitas Airlangga, 2022)
This article attempts to explain the influence of buya and religious issues on Jokowi’s vote decline in the 2019 Presidential Election (Pilpres) in West Sumatra. In the 2014 Presidential Election, Jokowi, who was paired with Jusuf Kalla, received 23.1 percent of the vote. However, in the 2019 Presidential Election, the vote share for Jokowi, who was paired with Ma’ruf Amin, fell to 14.1 percent. Ahead of the 2019 Presidential Election, there was a conflict between the buya in West Sumatra and Jokowi’s supporters regarding religious issues. This study used qualitative methods by relying on documentation studies related to the influence of the buya and religious issues ahead of the 2019 Presidential Election in West Sumatra. The study’s findings indicate that the buya and the majority of the people in West Sumatra practice modern Islam, while the vice-presidential candidate KH. Ma’ruf Amin practices traditional Islam. Religious issues in the form of the Islam Nusantara concept and the Sharia Regional Regulation (Perda) sharpen the difference between the buya and voters in West Sumatra with the Jokowi-Ma’ruf pair. It affected the defeat of Jokowi-Ma’ruf in West Sumatra in the 2019 Presidential Election.